Model based operator instructions using AR-technology - Hansson, Olga; Nadum, Osama (My University, 2019)
Augmented reality or (AR) is defined as a technology that provides a reality-based interface where users can interact with the real environment augmented with computer-generated images. The purpose of this report is to investigate the possibility of using AR in a specific assembly process of a product and to evaluate how it could be used in presenting information for operators at the assembly line. The project aims to provide an AR solution with a full analysis of the assembly process by testing, analyzing, and evaluating the proposed solution. The assembly process that is investigated in this report is an assembly of a drone. By using Vuforia Studio, an AR software computer-generated as an instruction for the assembly process. 12 participants were chosen to assemble the drone by using two different platforms. Microsoft Hololens, AR 3D eyewear device, and an Android Tablet were used as two distinctively different platforms in this experiment. The assembly process was analyzed and evaluated through observations and questionnaire provided to the participants. The experiment illustrated that AR can be used as a helpful instruction tool where all participants were able to fully assemble the drone. The Android Tablet platform participants showed slightly better performance due to familiarity with the device. During the experiment, different aspects of AR were explored including advantages, disadvantages, and limitations.